2020
DOI: 10.3390/ijerph17082677
|View full text |Cite
|
Sign up to set email alerts
|

Does the Proximity of Meals to Bedtime Influence the Sleep of Young Adults? A Cross-Sectional Survey of University Students

Abstract: Avoiding food before bedtime is a widely accepted sleep hygiene practice, yet few studies have assessed meal timing as a risk factor for disrupted sleep. This study examined the relationship between evening meal timing and sleep quality in young adults. A total of N = 793 participants (26% male) aged between 18 and 29 years responded to an online survey, which captured sociodemographic information, lifestyle variables, and sleep characteristics. Meal timing was defined as meals more than 3 h before or within 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
16
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 40 publications
0
16
1
Order By: Relevance
“… 21 Moreover, increased screen time leads to lower physical activity and thus low energy expenditure could be delaying the meal times and altering the sleep-wake rhythm. 9 , 27 , 28 In this context, a recent survey in Italian young age group individuals has also reported similar trend of delayed sleep-wake timings, time in bed and increase digital use during lockdown. 29 …”
Section: Discussionmentioning
confidence: 61%
“… 21 Moreover, increased screen time leads to lower physical activity and thus low energy expenditure could be delaying the meal times and altering the sleep-wake rhythm. 9 , 27 , 28 In this context, a recent survey in Italian young age group individuals has also reported similar trend of delayed sleep-wake timings, time in bed and increase digital use during lockdown. 29 …”
Section: Discussionmentioning
confidence: 61%
“…These facts seem like a contradiction and thus should be interpreted carefully. Past studies reported that meals within 3 hours of bedtime are positively associated with nocturnal awakening, 13 and that nocturnal awakening is associated to daytime sleepiness. 31 In light of these past studies, subjects in the patterns of ‘present to absent’ and ‘present to present’ may have had daytime sleepiness in 2014 due to lifestyle of supper close to bedtime, such daytime sleepiness may have lasted and thus they reported their poor SSQ in 2015.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated that poor SSQ is prevalent among individuals with unhealthy lifestyles, such as those with a lack of exercise and/or physical activity, 9 10 those who smoke 11 and/or engage in binge drinking 12 and those who eat meals close to bedtime. 13 However, it has not been clarified how SSQ is associated to changes in such lifestyles.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the study of existing the literature reveals that there are differences in sleep duration and quality in relation to sex of the adolescents. Cultural aspects such as differences in meal times, especially at dinner [ 35 ], as well as geographical location have shown that people living in the western part of a time zone have both later bedtimes and shorter sleep duration than people in the eastern area of a time zone [ 36 ]. Besides, different geographical locations of the participant cities place them in different time zones (Spain in central European standard time (CET), Estonia in Eastern European standard time (EET), and Iceland in Greenwich mean time (GMT)).…”
Section: Introductionmentioning
confidence: 99%